Transcriptome analysis of aerotolerant and aerosensitive Campylobacter jejuni strains in aerobic conditions - Delaporte, Elise; Karki, Anand B.; Fakhr, Mohamed K. (Frontiers in Microbiology, 2025)
Aerotolerance is vital for the survival of Campylobacter jejuni in the food supply, but the genetic mechanisms underlying aerotolerance remain unclear. This study compares differential gene expression in one aerotolerant and one aerosensitive strain of C. jejuni (WP2202 and T1-21 respectively) in aerobic vs. microaerobic conditions using RNA-Seq technology. The results show that the aerotolerant strain differentially regulated a greater number of genes under aerobic vs. microaerobic conditions as compared to the aerosensitive strain, particularly during the first 6 h of exposure. Differential analysis between aerobic and microaerobic conditions showed that COG category S (genes with unknown functions) had the highest number of DEGs across all timepoints in both strains. When category S was excluded, COG category J (translation, ribosomal structure, and biogenesis) had the highest number of DEGs between aerobic vs. microaerobic conditions with downregulated genes occurring at most timepoints in the two strains. Several previously characterized oxidative stress genes were differentially regulated in both strains in response to aerobic conditions. Both strains upregulated multiple heat shock genes in response to oxygen exposure, supporting the hypothesis that these genes might play a role in the oxidative stress response. A few genes involved in iron acquisition or transport were significantly upregulated under aerobic conditions in the aerosensitive strain, potentially forming reactive oxygen radicals due to increased iron levels. A spike in gene expression after 12 h of oxygen exposure was noted for both strains in various genes across the genome. This study demonstrates differences in differential gene expression between an aerotolerant and an aerosensitive strain in response to exposure to atmospheric oxygen and sheds light into understanding C. jejuni aerotolerance. Numerous genes with potential roles in C. jejuni aerotolerance were identified which provides new avenues for future research. In particular, the benefits and drawbacks of iron to the oxidative stress response and the links between the oxidative stress response and the expression of heat shock genes require further investigation.